A novel simulation calculation model based on photosynthetic electron transfer for microalgal growth prediction in any photobioreactor. (15th March 2023) - Wang, Zhenyi; Cheng, Jun; Guo, Danni; Chen, Lechong; You, Xuanxiang; Tang, Yang; Chen, Shutong; Chu, Feifei
Highlights: Light-effect colorimetric method was proposed to estimate f2 of suspended microalgae. A mathematical relationship between ETR and microalgal growth rate was identified. Average ETR of the cultivation system determined the microalgal CO2 tolerance. Cultivation system had a theoretical upper limit of biomass yield determined by ETR. A concept of biological similarity was proposed for scaling up microalgal experiment. Abstract: The microalgal research field is currently lacking a unified theoretical computing system to explain various experimental results related to microalgal growth. Thus a novel universal theoretical model was created to predict microalgal growth with carbon dioxide (CO2 ) fixation in any cultivation system. First, a new "light-effect colorimetric method" was proposed to estimate the actual f2 value of suspended microalgal cells during regular experimentation using a formula explaining the photosynthetic effective electron transfer rate (ETR = PFD·ΦII ·f1 ·f2 ), which only requires the use of a simple spectrophotometer. A mathematical relationship between photosynthetic electron transfer and the microalgal growth rate was then identified based on this modified ETR by simplifying factors influencing the cultivation conditions (e.g., nutrients and CO2 ) into the slope and intercept of this formula. Subsequently, software was written to allow the above relationship to stimulate any 3-D microalgal cultivation system. Many example cases were conducted to clarify the significance and application of this theoretical model. It was found that the average ETR of a cultivation system describes microalgal tolerance to high CO2 concentrations. A photobioreactor at any given location under a certain light condition has a theoretical maximum yield of microalgal biomass, irrespective of how the other cultivation conditions change. A new concept of "biological similarity" is proposed as a basic principle for scaling up microalgal experiments with photosynthetic CO2 fixation to perform a repeated growth curve with < 5 % error. Finally, a "multi-batch dilution method" was demonstrated to increase the microalgal biomass yield by 64.4 % over a short cultivation period. General application of this calculation model would change the empirical status of microalgal engineering designs.